Penyuluhan Pembangunan Ekonomi Lokal Melalui Produk Tradisional yang Berkualitas dan Berkelanjutan - Andrianto Prasetya Nugroho; Zulfa Zakiatul Hidayah; Fiqih Maria Rabiatul Hariroh; Hafsari Prabhamanik Faddila; Rizka Estisia Pratiwi (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2025)
Building the local economy through quality and sustainable traditional products at Khasanah Sari is a strategic step to improve community welfare and preserve culture. By addressing existing issues through training, digital marketing, product innovation and financial support, Khasanah Sari can grow and contribute positively to the local economy. Clear output targets will be a reference to measure the success of this initiative, making a positive impact on the community and the economy as a whole. Building a local economy through quality and sustainable traditional products involves community empowerment, product development and environmental sustainability By involving the community in production and marketing, their skills can be enhanced, creating new jobs. Traditional products need to be developed to meet quality standards that appeal to modern consumers, while using environmentally friendly raw materials and sustainable production techniques. Effective marketing, including the utilization of digital platforms, will help reach a wider market. In addition, collaboration between the government, businesses, and non-government organizations is essential to support development and market access. Public education and awareness on the importance of local products will also contribute to stronger economic growth and preservation of cultural heritage.bstract and Keywords must be written in English, in italic style, and contain a brief description of the research background, objectives, methods, findings, and implications. The abstract is written in one paragraph with a single space (maximum 200 words), without any reference or formula.